The Effects of Ageing and Visual Field Loss on Pointing to Visual Targets - Rubinstein, Nikki J. (Public Library of Science, 2014)
PURPOSE: To investigate the effect of ageing on visuomotor function and subsequently evaluate the effect of visual field loss on such function in older adults. METHODS: Two experiments were performed: 1) to determine the effect of ageing on visual localisation and subsequent pointing precision, and 2) to determine the effect of visual field loss on these outcome measures. For Experiment 1, we measured visual localisation and pointing precision radially at visual eccentricities of 5, 10 and 15° in 25 older (60–72 years) and 25 younger (20–31 years) adults. In the pointing task, participants were asked to point to a target on a touchscreen at a natural pace that prioritised accuracy of the touch. In Experiment 2, a subset of these tasks were performed at 15° eccentricity under both monocular and binocular conditions, by 8 glaucoma (55–76 years) and 10 approximately age-matched controls (61–72 years). RESULTS: Visual localisation and pointing precision was unaffected by ageing (p>0.05) and visual field loss (p>0.05), although movement time was increased in glaucoma (p = 0.01). CONCLUSION: Visual localisation and pointing precision to high contrast stimuli within the central 15° of vision are unaffected by ageing. Even in the presence of significant visual field loss, older adults with glaucoma are able perform such tasks with reasonable precision provided the target can be perceived and movement time is not restricted.